Depression in regard to postcovid syndrome - literature review - Kozińska, Iga; Oleszczuk, Rafał; Skwira, Sylwia; Gras-Ozimek, Aleksander; Kozińska, Anna; Oleszczuk, Anna (Journal of Education, Health and Sport, 2022)
Coronavirus disease-2019 (COVID-19) is a global pandemic health problem that causes a wide spectrum of clinical manifestations. Recovered patients who survive COVID-19 may continue to report a wide variety of clinical manifestations such as depression, which is named post covid syndrome. In our article, we sought to determine the frequency and possible causes of depressive symptoms and clinically-significant depression in the post COVID syndrome. We conducted a review of postcovid manifestations by searching PubMed, Scopus, World health organization (WHO) databases. The symptoms of postcovid syndrome have been shown as a weakness, cognitive impairment, sleep disturbance, and depression, among others. Persistent mental disorders among people who suffer from long-term COVID-19 may be related to psychological factors, as well as from infection and the associated neurobiological trauma. According to available studies, a significant percentage of depression symptoms is observed among people with postcovid syndrome, especially in older age groups. Also symptoms of mental, neurological and physical illness as well as inflammatory brain injury in people with post-COVID syndrome are likely to increase suicidal ideation and behavior in this patient population.